Efficient Learned Image Compression with Selective Kernel Residual Module and Channel-Wise Causal Context Model - Fu, Haisheng; Liang, Feng; Liang, Jie; Fang, Zhenman; Zhang, Guohe; Han, Jingning (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2024)
Recently, learning-based image compression approaches have achieved superior performance over classical image compression methods. However, their complexities remain quite high. In this paper, we propose two efficient modules to reduce the complexity. First, we introduce a selective kernel residual module into the core network, which effectively expands the receptive field and captures global information. Second, we present an improved channel-wise causal context model, designed to not only reduce encoding and decoding time but also ensure rate-distortion performance. Experimental results demonstrate that our proposed method achieves better tradeoff than recent leading learned image compression methods, and also outperforms the latest H.266/VVC (4:4:4) in terms of PSNR and MS-SSIM metrics.